Rabbi Shmuel Schneersohn of Lubavitch ("Maharash, " 1834–1882) and the False Twilight of Chabad Hasidism. Issue 2 (November 2021) - Rubin, Eli
Abstract : The maskilic characterization of the nineteenth century as a period of decline and ossification for Hasidism is increasingly eschewed by scholars, yet continues to mark current research in significant ways. As a case study, this article takes up Rabbi Shmuel Schneersohn of Lubavitch ("Maharash, " 1834–1882), rescrutinizing (1) the controversy surrounding the onset of his leadership, (2) his personality and charisma, (3) his methodological approach to the teachings and texts that he inherited from his predecessors, and (4) his theological contributions and their place in the broader trajectory of Chabad's intellectual history. His tenure emerges as a false twilight, in which a new foundation was laid for the perpetuation and expansion of Chabad-Lubavitch, as both an intellectual and activist movement, in the century that followed.